Plasma insulin response to oral carbohydrate in patients with glucose and lactose malabsorption. Issue 11 (November 1970) - Maxwell, J. D.; McKiddie, Margaret T.; Ferguson, Anne; Buchanan, K. D.
Abstract : Plasma insulin levels were determined following oral glucose in 12 patients with adult coeliac disease, after oral lactose in four patients with alactasia, and in age-matched control subjects. In coeliac patients the insulin response was greater than expected from the small rise in blood sugar, and no correlation was found between plasma insulin and sugar levels at any period during the test. The separation of the plasma insulin curve from the blood sugar curve after glucose is in keeping with the concept that a factor responsible for stimulating insulin secretion is released from the gut during or after absorption of glucose. In patients with selective lactose malabsorption (alactasia) administration of lactose by mouth failed to elicit any insulin response, indicating that the insulin-releasing effect of the bowel is not activated merely by the presence of intraluminal carbohydrate.